Expo 86, Vancouver, B.C., Canada - Saskatchewan Pavilion, Expo Centre, Canada Pavilion - Photo Graphics::::::::: (Agency Press)
The World's Fair has the prettiest site ever used for an exposition. These are three of the most remarkable and outstanding architectural wonders of Expo 86. The Saskatchewan Pavilion, Expo Centre and the Canada Pavilion.